(untitled) (Contemporary Journal of Social Science Review, 2025)
The objectives of the study were to find the level of Time Management Skills, Students’ Stress Levels and Academic Success, and to investigate the relationship and effect of Time Management Skills on Students’ Stress Levels and Academic Success at University Level. This research followed a survey research design within the positivistic philosophical paradigm. The target population included students from all public and private universities in Lahore district. The research instruments were questionnaires adapted from well-established scales. The validity of the questionnaires was confirmed through expert opinions, while reliability was assessed through pilot testing. For data analysis, SPSS was employed, using both descriptive statistics (Mean and S.D.) and inferential statistics (multivariate analysis and Pearson r). The findings of the study revealed that a strong positive correlation was found between time management skills and stress levels (r = .771, p < .01), showing that students with better time management reported higher stress, while moderate positive correlations emerged between time management and academic success (r = .417, p < .01). Stress levels were also moderately correlated with academic success (r = .420, p < .01), suggesting that manageable stress may act as a motivator for academic achievement, though excessive stress remains a risk. The predictive power was greater for stress reduction than for academic performance, implying that time management primarily protects psychological well-being while also contributing to, but not fully determining, academic achievement. It was recommended that Universities should design integrated workshops that combine time management training with stress management strategies, such as mindfulness and relaxation techniques.